The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/md.0000000000018657
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of salbutamol in the treatment of infants with bronchiolitis

Abstract: Background: To systematically evaluate the clinical efficacy of salbutamol treatment in infants with bronchiolitis. Methods: A systematic review and meta-analysis of randomized controlled trials (RCTs) investigating the use of salbutamol in infants with bronchiolitis was performed. The Cochrane Risk of Bias Assessment Tool was used to evaluate the quality of RCTs. Data were extracted and meta-analyzed using STATA version 12.0 (StataCorp, College Station… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
0
18
0
5
Order By: Relevance
“…And its use before this age can lead to adverse effects, such as high heart rate. 11 Similarly, studies have shown that the nebulized epinephrine is also not safe for routine use in infants with bronchiolitis. It should be considered in severe symptoms only.…”
Section: Methodsmentioning
confidence: 99%
“…And its use before this age can lead to adverse effects, such as high heart rate. 11 Similarly, studies have shown that the nebulized epinephrine is also not safe for routine use in infants with bronchiolitis. It should be considered in severe symptoms only.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, a previous meta-analyses of the efficacy of bronchodilator therapy in viral bronchiolitis showed modest short-term improvements in older infants (>12 months) [56,57]. Unfortunately, more recent meta-analysis have failed to include age subgroup analyses to confirm these previous findings [22,58]. However, when analysing the results of studies included in the National Institute for Health and Care Excellence (NICE) guidance on the diagnosis and management of bronchiolitis that recruited children 24 months or younger (as compared to those studies that included younger infants) [59], β 2 -AR agonists use was associated with significant improvements in outcomes such as accessory muscle score, oxygen saturation, respiratory rate [60], clinical respiratory scores [61,62] and respiratory distress [63].…”
Section: Host Factors Potentially Linked To Asm Hyperactivity and β 2mentioning
confidence: 99%
“…3 A meta-analysis showed that Beta 2-agonist therapy does not improve saturation of oxygen, does not lessen hospital stay, does not help in reducing hospitalization rate but can result in increased respiratory rate. 4 A trial conducted by Farooq A et al 5 in Islamabad showed that epinephrine could be a more effective treatment than salbutamol in the emergency management of acute bronchiolitis (mean RDAI score after 48 hours in the epinephrine group was 8.35±1.36 as compared to 10.07±1.37 in the salbutamol group). Another metaanalysis also showed the effectiveness and superiority of adrenaline over salbutamol.…”
Section: Introductionmentioning
confidence: 99%